Allergic rhinitis affects the duration of rapid eye movement sleep in children with sleep‐disordered breathing without sleep apnea. Issue 5 (19th February 2016) - Di Francesco, Renata C.; Alvarez, Jessica
Abstract : Background: Our goals were to assess whether allergic rhinitis (AR) is an aggravating factor that affects the severity of sleep apnea in children with tonsils/adenoid hypertrophy (T&A) and to compare polysomnographic data from children with and without AR. Methods: This prospective study included 135 children (age range, 3 to 14 years) with sleep‐disordered breathing (SDB) resulting from T&A. Children with lung, neurological, or craniofacial problems; septal deviations; previous pharyngeal surgeries; or orthodontic treatments were excluded. All children underwent a clinical evaluation, nasopharyngoscopy or lateral X‐ray imaging, sleep study, and hypersensitivity skin‐prick test. Results: The mean patient age was 6.44 ± 2.55 years (83 males). AR was present in 42.2% of the children; 40% presented with sleep apnea; and 17.04% had sleep apnea and AR. The percentage of time spent in the rapid eye movement (REM) sleep stage was lower among children with AR without sleep apnea ( p = 0.028); however, the percentage of REM sleep was not significantly different among children with apnea ( p = 0.2922). No difference in the apnea‐hypopnea index (AHI) was observed between the children with (AHI = 2.79 events/hour) and without AR (3.75 events/hour, p = 0.4427). A multivariate analysis showed that nasal congestion was an important factor that can affect the duration of the REM sleep stage. Conclusion: AR affects REM sleep in children with SDB without sleep apnea, and AR is not an aggravating factor regarding the severity of AHI.